Cultural Sustainability and Social Revitalization Through Performer Regeneration: A Case of Wayang Wong Sriwedari - Dwi Rahmani; Iwan Budi Santoso; Dwi Rahmani (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The field research conducted in this paper is situated against the backdrop of the need for traditional performing arts across the whole territory of Indonesia to adapt to contemporary social, cultural, and institutional conditions. Focusing on the Wayang Wong Sriwedari Javanese classical dance theater in Surakarta Indonesia, this study examines how intergenerational renewal drives artistic change and underpins cultural sustainability. Data was collected through interviews, field observations, and archival records. Preliminary findings show that young troupe members who have received formal arts education have adjusted the company’s stage composition, rehearsal processes, and social positioning. Recruiting within local government processes to help increase organizational stability and professionalization, giving even more power back to artistic collectives matched to these strategic interests locally. Furthermore, reimagined performance aesthetics embolden viewer engagement more broadly, the renewed public interest in traditional art forms is reflected in this developing sensibility. The extent and breadth of this evolution demonstrates that regeneration operates as an integrated multi-faceted set of approaches that draw on the intertwined processes of aesthetic making, civic and collective response. Some experts outline core arguments that heritage performing arts convincingly function as essential instruments for the restoration of society whenever duly supported by sound cultural policymaking and sustained participation from communities. Therefore, scholars should strive to embrace broader definitions of cultural sustainability that position it not simply as preservation but rather a dynamic continuum that intersects with regeneration in art and public interest in institutional governance and meaning.